Physical and Chemical Interplay Between the Membrane and a Prototypical Potassium Channel Reconstituted on a Lipid Bilayer Platform - Iwamoto, Masayuki; Oiki, Shigetoshi (Frontiers in Molecular Neuroscience, 2021)
Once membrane potential changes or ligand binding activates the ion channel, the activity of the channel is finely modulated by the fluctuating membrane environment, involving local lipid composition and membrane tension. In the age of post-structural biology, the factors in the membrane that affect the ion channel function and how they affect it are a central concern among ion channel researchers. This review presents our strategies for elucidating the molecular mechanism of membrane effects on ion channel activity. The membrane’s diverse and intricate effects consist of chemical and physical processes. These elements can be quantified separately using the lipid bilayer methods, in which a membrane is reconstructed only from the components of interest. In our advanced lipid bilayer platform (contact bubble bilayer, CBB), physical features of the membrane, such as tension, are freely controlled. We have elucidated how the specific lipid or membrane tension modulates the gating of a prototypical potassium channel, KcsA, embedded in the lipid bilayer. Our results reveal the molecular mechanism of the channel for sensing and responding to the membrane environment.